Inflammosomes and their role in pathology - Білозоров, О. П. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2014)
This review presents the literature data on intracellular macromolecular complexes "inflammosomes", playing an important role in regulating the formation and secretion of pro-inflammatory interleukins of IL-1 family and autoinflammatory diseases, the development of which is associated with increased activity of these complexes. The structure of various types of inflammosomes, mechanisms of their activation and involvement in the pathogenesis of various diseases as well as modern methods of correction of their functional activity are analyzed.